Analisis Tindak Tutur Asertif dan Ekspresif dalam Komik Pantun Kemelayuan Karya Shania Nur Avirsyah dan Sri Listiana Izar: Kajian Pragmatik - Rima Azrah Anggini; Sri Listiana Izar (Medan Resource Center, 2023)
This study aims to determine the types of assertive and expressive speech acts used in fiction books, namely Malay pantun comics. In this study, the speech is in the form of written media contained in the comic pantun. This study uses a pragmatic study that examines assertive and expressive speech acts. Assertive speech acts use Yule's approach which is divided into five, namely stating, suggesting, boasting, complaining, and claiming. While expressive speech acts use Rustono's approach which is divided into six, namely criticizing, complaining, praising, blaming, thanking, and congratulating. The research method used in this study is a qualitative descriptive method. The data in this study contained 23 types of assertive speech acts and 20 types of expressive speech acts contained in Malay pantun comics.